Peran Multidimensional Kantor Urusan Agama dalam Legalisasi Sertifikat Tanah Wakaf: Analisis Perspektif Hifzh Al-Mal Maqashid Asy-Syari'ah - Alhaq; Rifanto Ridwan; Aidah Rahmi; Nurma Yunita (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study is motivated by the high proportion of uncertified waqf land in Seberang Musi District, Kepahiang Regency, reaching 95 percent (31.19 hectares out of 44 locations), a condition that creates legal vulnerability for religious assets and risks inheritance disputes within wakif (waqf donor) families. This article analyzes the role of the Office of Religious Affairs (KUA) of Seberang Musi District in the legalization of waqf land certificates, identifies the procedures and constraints involved, and examines the implications of certificate legality for the legal resilience of wakif families and community welfare through the perspective of hifzh al-mal within maqashid asy-shari'ah. The study employed a descriptive qualitative field (juridical-empirical) method, with primary data drawn from in-depth interviews with the Head of KUA as PPAIW, Islamic religious extension officers, nazhir, wakif, community leaders, and village officials, analyzed using the Miles and Huberman model, with data trustworthiness maintained through source and technique triangulation. The findings show that KUA's role is multidimensional, functioning as PPAIW, educator, facilitator, and mediator; that the legalization procedure runs normatively but is hindered by a critical bottleneck in village-level land administration; and that certificate legality yields layered implications at the individual, communal, and economic levels which, read through hifzh al-mal, indicate achievement in the protective (difa'i) dimension while still requiring strengthening in the productive-development (tanmiyah) dimension of waqf